2020
DOI: 10.1155/2020/7170464
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA THAP9‐AS1 and TSPOAP1‐AS1 Provide Potential Diagnostic Signatures for Pediatric Septic Shock

Abstract: Background. Sepsis is a systemic inflammatory syndrome caused by infection with a high incidence and mortality. Although long noncoding RNAs have been identified to be closely involved in many inflammatory diseases, little is known about the role of lncRNAs in pediatric septic shock. Methods. We downloaded the mRNA profiles GSE13904 and GSE4607, of which GSE13904 includes 106 blood samples of pediatric patients with septic shock and 18 health control samples; GSE4607 includes 69 blood samples of pediatric pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…THAP9-AS1 is a recently annotated lncRNA and has been shown to be upregulated in pancreatic cancer and neutrophil apoptosis and downregulated in case of septic shock (35)(36)(37) . In this study, we have quantified THAP9 and THAP9-AS1 transcript expression under various stress conditions in the S-phase of cell cycle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…THAP9-AS1 is a recently annotated lncRNA and has been shown to be upregulated in pancreatic cancer and neutrophil apoptosis and downregulated in case of septic shock (35)(36)(37) . In this study, we have quantified THAP9 and THAP9-AS1 transcript expression under various stress conditions in the S-phase of cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…This leads us to speculate that there exists a stress specific regulation of THAP9 and THAP9-AS1 gene-pair that switches to THAP9-AS1 under stress conditions. This also might explain the upregulation of THAP9-AS1 in cancer cells which are naturally stressed (3537). Moreover, it is possible that both these genes play an unknown role in DNA repair and this might be responsible for their increased expression under certain stress conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another in vitro study demonstrated that NEAT1 was observed to regulate miR-495-3p/signal transducers and activators of transcription axis and miR-211/phosphoinositide-3-kinase/ protein kinase B axis in inflammatory process of sepsis (44). Even though the investigations for the roles of lncRNAs in septic shock are lacking, Wu et al identified lncRNA THAP9-AS1 and TSPOAP1-AS1 that might be of practical values for pediatric septic shock diagnosis (45). What is more interesting is that some lncRNAs like MALAT1, NEAT1, CRNDE, TUG1, and HOTAIR could exert therapeutic or diagnostic influence across different organ systems (Figure 1).…”
Section: The Roles Of Lncrnas In Sepsismentioning
confidence: 99%
“…Even though the investigations for the roles of lncRNAs in septic shock are lacking, Wu et al. identified lncRNA THAP9-AS1 and TSPOAP1-AS1 that might be of practical values for pediatric septic shock diagnosis ( 45 ). What is more interesting is that some lncRNAs like MALAT1, NEAT1, CRNDE, TUG1, and HOTAIR could exert therapeutic or diagnostic influence across different organ systems ( Figure 1 ).…”
Section: The Roles Of Lncrnas In Sepsismentioning
confidence: 99%